Influence of lemon skin powder on the mechanical and thermal properties of polyvinyl alcohol (PVA)/cassava starch biocomposites prepared by solution casting method - Salahuddin Junus; Revvan Rifada Pradiza; Muhammad Yusuf; Mahros Darsin; Gaguk Jatisukamto; Mochamad Asrofi (Universitas Mercu Buana, 2026)
More environmentally friendly alternative materials are needed to replace synthetic plastics to prevent environmental pollution. One biocomposite, a mixture of polyvinyl alcohol (PVA) and cassava starch, is an appropriate solution; however, its mechanical properties are low. Lemon skin, which is often considered waste, contains promising cellulose and phenolic extract content, making it a potential superior and functional filler for biocomposites, particularly in active packaging applications. This study presents an investigation into the use of lemon skin powder (LSP) as a filler for PVA- and cassava starch-based biocomposites. The biocomposites were prepared using the solvent casting method by varying the concentration of lemon skin powder filler, namely 0%, 1%, 3%, and 5%, with the final product being a film. Analysis was carried out on the mechanical properties, morphology (Scanning Electron Microscopy (SEM)), and thermal properties of the film. The results show that the mechanical properties of the film increased when LSP was added, with the highest tensile strength of 13.82 MPa for biocomposite films containing 5% LSP compared to the tensile strength of pure PVA and PVA/cassava starch blends. In addition, the thermal properties of biocomposites also increased at this content, as evidenced by an increase in the initial decomposition temperature. Specifically, the initial decomposition temperature of pure PVA, which was 204°C, increased to 214°C in biocomposites with 5% LSP. This improvement in thermal properties and tensile strength can be attributed to the strong interfacial bonding between the filler and the matrix, which contributes to the overall compact structure of the biocomposite. Morphological observations confirm the increased interface interaction and uniformity of filler distribution in the composite. These results confirm that lemon skin fibers have positive potential as reinforcements for PVA and cassava starch-based biocomposites, particularly in food packaging applications.